THE HIGH PLASMA RETINOL BINDING PROTEIN 4 LEVEL AS A RISK FACTOR CONSEQUENTLY OF TYPE 2 DIABETES MELLITUS OF ABDOMINAL OBESITY - Budhitresna, AAG; Suastika, Ketut; Mantik Astawa, Nyoman; Santoso, Anwar (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Abdominal obesity (Ab-Ob) related to cardiometabolic risk, that is riskfactor constellation for succeeded cardiovasculer disease and type 2 DiabetesMellitus (DM). That factors such as atherogenic dislipidemia, hypertension,hyperglycemia, protrombotic state, and proinflammation state. Type 2 DMcharacterised by insulin resistance (IR). Plasma levels of retinol binding protein 4(RBP4) that is secreted by adipocytes are increased in insulin resistance (IR) state.Experiment in mice suggest that elevated RBP4 level cause IR. Although theunderlying mechanism is not clearly understood, RBP4 considered playimportance role consequently of type 2 DM in Ab-Ob.This research was carried out to determine the role of high plasma RBP4level as a risk factor consequently of type 2 DM in Ab-Ob. The research wasconducted by cross sectional analytic in 81 patients with Ab-Ob and case controlstudy with matching on 33 patients with Ab-Ob type 2 DM as cases and 33patients with Ab-Ob non type 2 DM as control. The plasma of TNF-?, sTNFR1,and RBP4 levels was measured by ELISA. IR status of the patients wasdetermined by HOMA-IR, whereas the ?-cell function was determined byHOMA-B. Ab-Ob was defined by using criteria for Asian peoples (male WC ? 90cm; female WC ? 80 cm). The result of 81 patients with Ab-Ob showed that bothplasma of TNF-? and sTNFR1 levels were significant positive correlated withplasma RBP4 level (coeficient correlation r = 0,294; p = 0,008 dan r = 0,458; p =<0,001 respectively). In addition, the plasma of RBP4 level significantly positivecorrelation with HOMA-IR (r = 0,450; p = 0,000) and significantly negativecorrelation with HOMA-B (r = -0,564; p = <0,001). In the matched case-controlstudy, it was shown that mean plasma of RBP4 level of type 2 DM group (76,08 ±16,84 ?g/ml) statistically higher than that without type 2 DM group (41,13 ±14,75 ?g/ml) (p = <0,001). The odds ratio higher plasma of RBP4 level was 5,426(CI 95%; 1,343 – 21, 928) statistically significant for increases risk type 2 DM (p= < 0,05). It has been proven that RBP4 was a dominant and consisten risk factor(66.9%, p = < 0.001) which influenced the incidence of type 2 DM in Ab-Ob. It can be concluded that high plasma of RBP4 level have a greater risk tosuffered from type 2 DM compared to low plasma of RBP4 in Ab-Ob. The highplasma of RBP4 level is most dominant and consistent risk factor consequently oftype 2 DM. These mechanism could behind the association between high plasmaof RBP4 level and type 2 DM.
Keywords: Abdominal obesity, RBP4, HOMA-IR, HOMA-B and type 2 DM.